Open Innovation and Regulatory Challenges in New Modality Development: The Pivotal Role of Contract Development and Manufacturing Organisations in Advancing Antibody Drugs. - Yoshiura, Hiromu; Kawata, Yayoi; Sengoku, Shintaro (Therapeutic Innovation & Regulatory Science, 2025)
Background: Ensuring regulatory-compliant manufacturing capability is an essential challenge for new treatment modalities, but its internalisation is not easy for pharmaceutical companies, especially start-ups. This study examines the functions and requirements of contracted development and manufacturing organisations (CDMOs) using the development process of antibody medicines as a case study. Methods: Utilizing PubMed, Cortellis and Patent Integration databases, this study delves into publication and contractual trends in monoclonal antibody drugs (mAbs) development, alongside an analysis of patent filings by CDMOs, offering a comprehensive overview of the evolving landscape in mAbs innovation. Results: In the early stages of mAbs development, dedicated bio firms (DBFs) led R&D with superior drug discovery technology but lacked manufacturing capability, which was complemented by CDMOs. This collaboration was an opportunity for CDMOs to expand their capabilities beyond manufacturing technology into antibody drug candidate discovery and structural optimisation technology. From mid-development onwards, it established a technology platform based on these capabilities and developed and established partnerships with existing pharmaceutical companies, including mega pharma. Conclusions: The impact of institutions and regulations on the innovation process was assessed during this development process. These findings are expected to provide valuable insights into the innovation system for new modalities.